157 Prevalence of Aortic Valve Abnormalities in the Elderly: A Screening Study Using Hand-Held Ultrasound Scanni. (3rd June 2016) - Williams, Catrin; Maskell, Nicholas; Rees, Emma; Truman, Kirstie; Ionescu, Adrian
Abstract : Background: Degenerative aortic stenosis (AS) is increasingly recognised and treated with valve replacement in the elderly. The advent of percutaneous aortic valve intervention (TAVI) has opened opportunities for treatment in patients who would have been turned down for surgery just a few years ago, with a commensurate increase in health care-associated costs. However, there is a relative lack of data regarding the prevalence of AS in this very group of older patients, which can make planning and delivery of a TAVI service difficult. Aim of the study We set out to investigate the prevalence of aortic valve abnormalities by performing echocardiography with a hand-held scanner in elderly patients attending a large GP surgery for non-cardiac reasons. We hypothesised that a strategy of echo screening for AV abnormalities in this population would have a high yield in detecting clinically relevant pathology. Methods: One hundred consecutive patients aged >75years old who had no history of a heart murmur, myocardial infarction or heart failure had a detailed echocardiographic exam using a hand-held scanner without spectral Doppler capabilities. Cardiac risk factors were documented. We classified aortic valves as normal, aortic sclerosis (thickened leaflets without restriction) and aortic stenosis (thickened, restricted leaflets). Qualitative LV function assessment and colour Doppler assessment of aortic and mitral regurgitation were also obtained. Results: The mean age was 78.3 (8.7) years. The quality of the images was good in 74 studies, moderate in 20 and poor in 6. We found 48 normal valves, 28 cases of aortic sclerosis and 24 of aortic stenosis (of which 4 moderate and 1 severe). Aortic regurgitation was present in 35 cases (30 mild, 5 moderate), and LVEF was normal in 92 subjects, mildly impaired in 6 and moderately impaired in 2. There were 2 cases of severe MR and 4 of moderate MR, all organic. Neither cardiac risk factors nor mitral annular calcification were associated with aortic sclerosis or stenosis. Conclusions: Our preliminary data suggest that a strategy of echocardiographic screening in patients >75years of age identifies a significant number of abnormalities that require formal cardiology follow-up or work up for intervention, including a 5% prevalence of moderate or severe AS, and 6% prevalence of moderate or severe MR.